UNRAVELING THE SEMANTIC STRUCTURAL FEATURES OF NEGATIVE EVALUATION EXPRESSIVE VERBALIZERS IN FOREIGN LANGUAGES (American Journal of Interdisciplinary Research and Development, 2024)
This article meticulously examines the semantic and structural features of negative evaluation expressive verbalizers in foreign languages, focusing on Spanish, Mandarin, and German as representative examples. The exploration aims to uncover the nuanced ways in which disapproval, criticism, or disappointment is linguistically conveyed across diverse cultural and linguistic contexts. Through a comparative analysis, the article delves into lexical choices, sentence structures, and cultural nuances, shedding light on the intricate strategies employed to express negativity.